Determinants of transient and persistent hospital efficiency: The case of Italy. (21st September 2017) - Colombi, Roberto; Martini, Gianmaria; Vittadini, Giorgio
Summary: In this paper, we extend the 4‐random‐component closed skew‐normal stochastic frontier model by including exogenous determinants of hospital persistent (long‐run) and transient (short‐run) inefficiency, separated from unobserved heterogeneity. We apply this new model to a dataset composed by 133 Italian hospitals during the period 2008–2013. We show that average total inefficiency is about 23%, higher than previous estimates; hence, a model where the different types of inefficiency and hospital unobserved characteristics are not confounded allows us to get less biased estimates of hospital inefficiency. Moreover, we find that transient efficiency is more important than persistent efficiency, as it accounts for 60% of the total one. Last, we find that ownership (for‐profit hospitals are more transiently inefficient and less persistently inefficient than not‐for‐profit ones, whereas public hospitals are less transiently inefficient than not‐for‐profit ones), specialization (specialized hospitals are more transiently inefficient than general ones; i.e., there is evidence of scope economies in short‐run efficiency), and size (large‐sized hospitals are better than medium and small ones in terms of transient inefficiency) are determinants of both types of inefficiency, although we do not find any statistically significant effect of multihospital systems and teaching hospitals.